Vero Cell Proteomic Changes Induced by Zika Virus Infection. Issue 4 (23rd January 2019) - Glover, Kathleen K. M.; Gao, Ang; Zahedi‐Amiri, Ali; Coombs, Kevin M.
Abstract: The re‐emergence and the recent spread of the Zika virus (ZIKV) has raised significant global concerns due to lack of information in patient diagnosis and management. Thus, in addition to gaining more basic information about ZIKV biology, appropriate interventions and management strategies are being sought to control ZIKV‐associated diseases and its spread. This study's objective is to identify host cell proteins that are significantly dysregulated during ZIKV infection. SOMAScan, a novel aptamer‐based assay, is used to simultaneously screen >1300 host proteins to detect ZIKV‐induced host protein dysregulation at multiple time points during infection. A total of 125 Vero cell host proteins, including cytokines such as CXCL11 and CCL5, interferon stimulated gene 15, and translation initiation factors EIF5A and EIF4G2, are significantly dysregulated after ZIKV infection. Bioinformatic analyses of 77 host proteins, that are significantly dysregulated ≥1.25‐fold, identify several activated biological processes, including the JAK/STAT, Tec kinase, and complement cascade pathways.